Comparative production performance of vegetable crops in the country vis-à-vis Eastern India - Ahmad, Nasim; Sinha, DK; Singh, KM; Mishra, RR (Vegetable Science, 2018)
The present study was conducted to analyze thecomparative production performance of vegetable crops in eastern India and India. In this study compound growth rates of vegetable crops and major vegetables like potato, tomato, onion, brinjal, cabbage, cauliflower, okra and pea were calculated by fitting exponential function to variables like area, production and productivity and tabular analysis was done to arrive at meaningful results. The study was based on macro framed data collected through different published secondary sources like Horticultural statistics of India and Agricultural statistics at a Glance, Ministry of Agriculture and Farmers Welfare, Government of India. The results pointed out positive growth trends in area, production and productivity of vegetable crops in the region and country during the last 16 years. Considering remarkable growth trends, vegetable crops may be taken as pathway for income enhancement of farming communities. Being good sources of healthy dietary requirements, nutritional security of the region in particular and nation in general can be addressed. Some limiting factors like pre and post harvest losses, storage facilities, lack of refrigerated vans and transportation and farmer’s friendly marketing facilities restrict arrival of the actual quantity of vegetable to theconsumers and in fetching remunerative prices of the produce. Hence, there is a need to improve pre and postharvest technologies, provide suitable transport and marketing facilities. Appropriate policy to tackle the abrupt price fluctuations during good harvest and scarce period is also needed to protect both the producers and the consumers. Shifting Indian farming from rural setup to urban setup and linking cultivators to super markets particularly for vegetables grower will be a key drivers in improving financial conditions of the farming community of country.